1991
DOI: 10.1093/nar/19.20.5619
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanism of interaction of simian Ku protein with DNA

Abstract: Ku protein is a relatively abundant DNA-binding protein which was first detected as the autoantigen in a patient with scleroderma-polymyositis overlap syndrome (hence the name 'Ku'). It is a heterodimer of two polypeptide chains of molecular weights 85,000 and 72,000, and it characteristically binds, in vitro, to the ends of DNA fragments, and translocates to form regular multimeric complexes, with one protein bound per 30 bp of DNA. We have studied the mechanism of interaction of Ku protein with DNA in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
159
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 22 publications
7
159
0
Order By: Relevance
“…Ku is capable of binding to hairpin structures, single-stranded nicks, and gaps in an apparently sequence-independent manner (44)(45)(46)61). A number of studies have also suggested that the Ku protein is capable of sequence-specific DNA binding (36)(37)(38)(39)(40)60).…”
Section: Discussionmentioning
confidence: 99%
“…Ku is capable of binding to hairpin structures, single-stranded nicks, and gaps in an apparently sequence-independent manner (44)(45)(46)61). A number of studies have also suggested that the Ku protein is capable of sequence-specific DNA binding (36)(37)(38)(39)(40)60).…”
Section: Discussionmentioning
confidence: 99%
“…In all of the above studies, the r R N A promoter was positioned close to the end of the linear D N A molecule. Although D N A ends are required for the initial binding of K u / D N A -P K to DNA, previous reports have suggested that once bound to the template, it can then translocate to internal positions on the D N A molecule (de Vries et al 1989;Paillard and Strauss 1991;Gottlieb and Jackson 19931. We were thus prompted to test w h e t h e r transcriptional i n h i b i t i o n was affected by the location of the D N A ends in regard to the transcription complex.…”
Section: Dna-pk and The Pol I Transcription Complex Must Be Colocalizmentioning
confidence: 99%
“…Ku, originally identified as an antigen recognized by sera from various autoimmune patients, is a moderately abundant nuclear protein comprising polypeptides of -70 and 80 kD in a tightly associated heterodimeric complex (Francoeur et al 1986;Mimori and Hardin 1986;Yaneva and Busch 1986;Reeves and Sthoeger 1989). Although some selective interactions with defined promoter elements have been described, most evidence indicates that Ku binds DNA in an essentially sequence-independent fashion (Mimori and Hardin 1986;de Vries et al 1989;Paillard and Strauss 1991;Zhang and Yaneva 1992;Blier et al 1993).…”
mentioning
confidence: 99%
“…Complex 1 is thought to result from binding of a single rKu to the dsDNA, while complex 2 is likely to contain 2 rKu per 48 bp duplex. Ku is thought to require a minimum of 20-25 bp for stable binding, and loading of multiple Ku molecules onto longer strands of duplex DNA has been observed [16]. It is worth noting that Figure 3A shows that at 7.7 nM Ku all of the 5 nM labeled DNA substrate has been bound, suggesting that a high percentage of the rKu is DNA-binding active.…”
mentioning
confidence: 96%